mRNA localization in Caenorhabditis elegans embryogenesis - Parker, Dylan M., author; Osborne Nishimura, Erin, advisor; Ben-Hur, Asa, committee member; Montgomery, Tai, committee member; Stasevich, Tim, committee member; Santangelo, Tom, committee member (Colorado State University. Libraries, 2021)
From guiding cell specification to regulating protein output, post-transcriptional regulation of mRNA is essential for life. As a result, many mechanisms underlying post-transcriptional regulation are highly conserved across the kingdoms of life. As the spatial resolution of microscopy and sequencing assays has increased, mRNA localization has emerged as a prevalent form of post-transcriptional regulation directing various cellular processes. Perhaps most notably, our understanding of post-transcriptional mRNA regulation and cellular function as a whole has been revolutionized by the discovery that many well-studied mRNA foci, such as germ granules, P-bodies, and stress granules, do not follow the lock-and-key principle of stoichiometric complex formation, but are actually phase-separated, biomolecular condensates. Due to their liquid-like nature, biomolecular condensates can aggregate or disperse component transcripts and proteins with exquisite environmental and temporal sensitivity. As a result, biomolecular condensates can regulate myriad processes as varied as co-translationally organizing protein components for complex assembly (Budding yeast translation factor mRNA granules), reinforcing translation inhibition (Germ granules) or activation (Neuronal granules), and facilitating the organization of other organelles (Axonemal dynein foci/kl-bodies). While an influx of studies have provided insights into the function of well-studied and novel biomolecular condensates alike, much remains unknown. What factors govern assembly and disassembly of condensates? How do they interact with one another? Is condensation the cause or consequence of the functional regulation of any particular mRNA? To begin to answer these questions, this thesis defines Caenorhabditis elegans as a model organism for exploring mRNA localization, its mechanisms, and its functions with a focus on condensate transcripts. Thus, the discoveries made have contributed to the fields of post-transcriptional gene regulation, mRNA localization, and condensate biology by elucidating mechanisms of localization, improving on methods of observing localization patterns, and establishing C. elegans as a tractable model for exploration of mRNA localization.